Determinan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Pekauman Kota Banjarmasin - Norfai Norfai; Abdullah Abdullah (Jurnal Akademika Baiturrahim Jambi, 2021)
This research is an analytic survey with a Case Control approach with a ratio of 1:1. The sample size was 92 respondents with Purposive Sampling technique. Data collection on stunting events in infants was obtained from secondary data captured at Pekauman Public Health Services, while data on maternal age, maternal education level, maternal height, history of birth weight, exclusive breastfeeding, completeness of basic immunizations, parity, family income and history of pregnancy KEK (chronic energy deficiency) were obtained with the interview method using a questionnaire. Data were analyzed univariate maternal statistics, bivariate statistical Chi Square test statistically there was no relationship between using age, maternal height, history of birth weight, exclusive breastfeeding, completeness of basic immunizations, parity, family income, and history of  pregnancy KEK (chronic energy deficiency) with stunting in children under five years. Statistically there is a significant relationship between mother's education level and the incidence of stunting in children under five years in Banjarmasin Pekauman Public Health Services working area. The mother's education level variable is the dominant variable with Odds Ratio of 2.072. Odds Ratio 2.072 means that the low level of education of mothers has the risk of stunting and multivariate statistical tests using the enter method using a computer program with a 95% confidence level. Based on the results of the study it was found that in infants by 2,072 times greater than the mother's high level of education. It is recommended that comprehensive and intensive education about parenting during the First 1,000 Days of Life is needed, in order to be able to change the mindset of mother who have children under five years about the importance of nutrition in children under five years to health